Implementasi Keputusan Menteri Agama Nomor 154 Tahun 1991 Terhadap Inpress Nomor 1 Tahun 1991: The Implementation of the Minister of Religious Affairs Decree No. 154 of 1991 in Relation to Presidential Instruction No. 1 of 1991 - Syaifuddin Syaifuddin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
The enactment of the Islamic Law Compilation (KHI) through Presidential Instruction No. 1 of 1991, followed by the Decree of the Minister of Religious Affairs No. 154 of 1991, prompted concrete responses from religious institutions in Indonesia. This study aims to describe and evaluate the implementation of KHI socialisation by three institutions in Jember Regency: the Religious Court, the Department of Religious Affairs, and STAIN. Using a qualitative approach with an evaluative case study design, data were collected through structured interviews, observation, and documentation. The findings indicate that all three institutions responded proportionately to their respective roles. The Religious Court utilised cross-institutional channels and internal court activities; the Department of Religious Affairs worked through KUA and cultural approaches; while STAIN integrated socialisation into the tri-dharma of higher education. Key constraints included limited funding, inadequate infrastructure, time constraints, and low public understanding of fiqh. In conclusion, KHI socialisation remains suboptimal, requiring sustainable funding, the distribution of KHI books to community leaders, and the strengthening of student roles beyond community service programmes. Pemberlakuan Kompilasi Hukum Islam (KHI) melalui Inpres Nomor 1 Tahun 1991 dan ditindaklanjuti KMA Nomor 154 Tahun 1991 menuntut respons nyata dari institusi keagamaan di Indonesia. Penelitian ini bertujuan mendeskripsikan dan mengevaluasi implementasi sosialisasi KHI oleh tiga institusi di Kabupaten Jember: Pengadilan Agama, Departemen Agama, dan STAIN. Menggunakan pendekatan kualitatif dengan desain studi kasus evaluatif, data dikumpulkan melalui wawancara terstruktur, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa ketiga institusi telah merespons kebijakan secara proporsional sesuai peran masing-masing. Pengadilan Agama memanfaatkan jalur lintas instansi dan kegiatan internal persidangan; Departemen Agama melalui KUA dan pendekatan kultural; sementara STAIN mengintegrasikan sosialisasi ke dalam tridarma perguruan tinggi. Kendala utama meliputi keterbatasan dana, sarana prasarana, waktu, serta rendahnya pemahaman masyarakat terhadap fikih. Kesimpulannya, sosialisasi KHI belum optimal dan perlu pendanaan berkelanjutan, distribusi buku KHI kepada tokoh masyarakat, serta penguatan peran mahasiswa di luar KKN.